Phylogenetic Prediction of Alternaria Leaf Blight Resistance in Wild and Cultivated Species of Carrots - Arbizu Berrocal, Carlos Irvin (2017)
Plant scientists make inferences and predictions from phylogenetic trees to solve scientific problems. Crop losses due to disease damage is an important problem that many plant breeders would like to solve, so the ability to predict traits like disease resistance from phylogenetic trees derived from diverse germplasm would be a significant approach to facilitate cultivar improvement. Alternaria leaf blight (ALB) is among the most devastating diseases of carrots (Daucus spp., Apiaceae) worldwide. Thus, new approaches to identify resistant germplasm to this disease are needed. In a study of 106 accessions of wild and cultivated Daucus and related genera, we determined plant height is the best explanatory variable to predict ALB resistance using a phylogenetic linear regression model. Using the estimated area under the disease progress curve, the most resistant species to ALB were the non-carrot relative Ammi visnaga (L.) Lam. and the wild carrot relative D. crinitus Desf. A permutation tail probability test was conducted considering phylogenetic signal to evaluate the strength of association between the Daucus phylogeny and ALB resistance. We found that species belonging to clade A, which includes carrots and other Daucus possessing 2n = 18, 20, or 22 chromosomes, are slightly more resistant to ALB than members of other clades of the Daucus phylogeny.